Role of Participation and Awareness to Cooperative in Common Property Institution Management: A Case Study of Forest in Aceh, Indonesia - Gudria .; Salfarina Abdul Gapor (Aceh International Journal of Social Science, 2013)
Abstract - This paper reviews some of the central concerns and findings of writings on forests as they related to the theoretical ambitions of commons scholars, and to efforts to govern forests more sustainably and equitably in Aceh. The review is especially important in the context of unfolding efforts to govern forests in new ways over the past three decades cause conflict between Government Republic of Indonesia and Free of Aceh Movement. However, as important as the review is an assessment of the achievements of this literature, existing blind spots, and potential new areas of exciting research and investigation. The review suggests specific areas in relation to methods, data, and theories of common property that will advance the field further. It would be no exaggeration to say that the study of forests as commons has been central to the development of scholarship on common property. Equally certainly, the interest in forests has generated a vast corpus of research outside the field of common property. The magnitude, variety, and depth of this body of research is an accurate reflection of the many different ways in which forests have been and continue to be central to human survival, livelihoods, and prosperity. Keyword        : Free of Aceh Movement, Government Republic of Indonesia, common property, conflictPaper Type   : Research Paper